PERTANGGUNGJAWABAN HUKUM PENYELENGGARA SECURITIES CROWDFUNDING TERHADAP PEMODAL EFEK BERSIFAT UTANG ATAU SUKUK - Indramayu Indramayu; Yeni Salma Barlinti (Universitas Suryakancana, 2022)
Technological developments have encouraged the creation of Securities Crowdfunding (SCF) in Indonesia predicted to continue to grow. In contrast to Equity Crowdfunding, Securities that can be offered in SCF can be in the form of Debt Securities or Sukuk (EBUS). The broker's performance as the power of attorney of an EBUS Investor can determine the success of the EBUS investment. What is the legal relationship between Debt Investor and broker? and what are the legal liability of broker as the Investor’s power of attorney? are the research questions. This research used a doctrinal research with qualitative data analysis. The results showed that the legal relationship between the broker and the EBUS Investor is contractual and legal relationship, in addition to the legal liability that can be requested to broker is contractual liability and tort law. So, if the broker has neglected to do its responsibilities and it causes the EBUS Investor to suffer losses, then the EBUS Investor can sue the broker for a default or a tort law. The Financial Services Authority needs to socialize the concept of broker’s responsibilities and oversee the implementation of the OJK regulation number 57 of 2020 to provide protection to EBUS investors. Keywords : Legal Liability, Securities Crowdfunding, EBUS, Broker and Investors.